ESL teachers' readiness in the teaching and learning of literature / Wilarmy Geniron Jebron - Wilarmy, Geniron Jebron (2011)
Malaysian English teachers are expected to teach not only the English language but also literature in the English as a Second Language (ESL) setting. They are greatly challenged as they are in a setting that needs a lot of enthusiasm and interest. This study was designed to discover ESL Teachers’ Readiness in the Teaching and Learning of Literature. Therefore, the aims of this study were to investigate the significant difference between male and female ESL teachers’ readiness in the teaching and learning of the literature component, to indicate the levels of the ESL teachers’ readiness in the teaching and learning of the literature component and finally to highlight the most contributing factor to ESL teachers readiness in the teaching and learning of the literature component. For the purpose of this study, quantitative research was utilized in which questionnaire was used to collect data. The data was analyzed using a t-test and one-way ANOVA. The survey research design in this research involved 143 ESL teachers who were teaching literature at 20 secondary schools in Kuching Division, Sarawak. From the analysis of findings it was found that there was no significant difference between male and female ESL teachers’ readiness in the teaching and learning of the literature component, almost 95% of the respondents agreed that proficiency was sufficient to the teaching and learning of literature and 90% of them also believed that they were confident to teach literature. All the five nullhypotheses in this study were accepted and the most contributing factor to ESL teachers regarding their readiness to teach literature was the training and courses attended. Therefore, it was concluded that ESL teachers in this study were ready in the teaching and learning of literature. The discussion, implications of the study and suggested pedagogical framework were also mentioned in this study.